HIV-related Sexual Risk Taking Among HIV-negative Men Who Have Sex with Men in Zagreb, Croatia - Štulhofer, Aleksandar; Božičević, Ivana; Begovac, Josip; Baćak, Valerio (2008)
Croatia has a low-level HIV epidemic and, as in a number of other Central and Southeastern European countries, sex between men accounts for most HIV infections. This study examines sexual behavior and the correlates of condom use in a snowball sample of 342 HIV non-infected men who have sex with men (MSM) in Zagreb. The median age of participants in the sample was 27 years. The majority of participants (81%) reported using condom at last anal sex with casual partner and 56% claimed to have used condoms consistently at anal sex with casual partners in the last 12 months. HIV risk self-assessment and number of sexual partners were significantly correlated with condom use at last anal sex with casual partner. Self-assessed HIV-risk and heterosexual activity were found associated with consistent condom use at anal sex with casual partners. To sustain a low-level HIV epidemic, targeted intervention among young MSM is needed in Croatia.
Projekt MZOS
Projekt MZOS
Projekt MZOS
ENG